The Pessimist Rearmed: ŽiŽek on Christianity And Revolution - Paik, Peter Y. (My University, 2004)
The author examines the works of ŽiŽek, Kierkegaard, and contemporary entertainment in order to explore revolution and Christianity. A main focus is on sacrifice, and how side effects of an aspiration can be greater than the aspiration itself.
Keywords: Marxism; Kierkegaard; ŽiŽek; Christianity; sacrifice; politics; revolution